Recovery of the first full-length genome sequence of a parapoxvirus directly from a clinical sample - Thomas Günther (Nature Portfolio, 2017)
Abstract We recovered the first full-length poxvirus genome, including the terminal hairpin region, directly from complex clinical material using a combination of second generation short read and third generation nanopore sequencing technologies. The complete viral genome sequence was directly recovered from a skin lesion of a grey seal thereby preventing sequence changes due to in vitro passaging of the virus. Subsequent analysis of the proteins encoded by this virus identified genes specific for skin adaptation and pathogenesis of parapoxviruses. These data warrant the classification of seal parapoxvirus, tentatively designated SePPV, as a new species within the genus Parapoxvirus.